Experimental Modal Analysis and Operational Deflection Shape Analysis for Kenyir Dam Spillway Physical Model - Hassan N.H.; Zawawi M.H.; Mazlan A.Z.A.; Abas M.A.; Zainol M.R.R.M.A.; Radzi M.R.M.; Kamaruddin M.A. (Springer Science and Business Media Deutschland GmbH, 2025)
Kenyir Dam spillway physical model was developed to determine the vibration characteristics of the dam spillway due to different spilling events. This study focused on determining the natural frequency of the dam spillway in order to compare it with the mode shape due to spilling events. The physical model scale was 1:50 and similitude analysis using Froude law was used for scaling down purposes. There were 2 different water levels simulated for the experiment which were 2.92 and 2.96m, and for each water level spilling, operational deflection shape (ODS) analysis was done for the spillway body. The most dominant mode shape was observed at the wall of the spillway at the downstream area. This mode shape corresponded to the natural frequency of 2801.1Hz and cause an overall deflection amplitude of 0.353m for a water level of 2.96m. The numerical analysis was completed in order to compare the experimental result and it showed that the percentage differences for all parts were below 10%, which is generally below an allowable error percentage. The conclusion from this study was the experimental natural frequencies and mode shapes for all the parts show good agreement with the numerical analysis of vibration characteristics of Kenyir Dam spillway physical model. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.